A new Kho-Kho optimization Algorithm: An application to solve combined emission economic dispatch and combined heat and power economic dispatch problem. (September 2020) - Srivastava, Abhishek; Das, Dushmanta Kumar
Abstract: In this article, a new optimization technique known as Kho-Kho optimization (KKO) algorithm is presented. This proposed technique is a population based meta-heuristic method which is inspired from the strategies used by players in a well known tag-team game played in India, i.e. Kho-Kho. The performance and superiority of the proposed method with respect to other existing methods is evaluated using twenty nine benchmark functions and real-time optimization problems related to power system i.e. combined emission economic dispatch and combined heat and power economic dispatch problem. Highlights: This paper presents a new Kho-Kho optimization algorithm (KKO). KKO is inspired by a well-known tag-team game played in India known as Kho-Kho. KKO mimics the strategies used by a chasing team to catch the runners of a running team. Twenty-nine benchmark functions are used to test the performance of the proposed algorithm. Further, KKO is used to solve real-time optimization problems of power system.